Isoforms of the Papillomavirus Major Capsid Protein Differ in Their Ability to Block Viral Spread and Tumor Formation - Hasche, Daniel; Ahmels, Melinda; Braspenning-Wesch, Ilona; Stephan, Sonja; Cao, Rui; Schmidt, Gabriele; Müller, Martin; Rösl, Frank (Frontiers in Immunology, 2022)
Notably, the majority of papillomaviruses associated with a high cancer risk have the potential to translate different isoforms of the L1 major capsid protein. In an infection model, the cutaneous Mastomys natalensis papillomavirus (MnPV) circumvents the humoral immune response of its natural host by first expressing a 30 amino acid extended L1 isoform (L1LONG). Although inducing a robust seroconversion, the raised antibodies are not neutralizing in vitro. In contrast, neutralizing antibodies induced by the capsid-forming isoform (L1SHORT) appear delayed by several months. We now provide evidence that, although L1LONG vaccination showed a strong seroconversion, these antibodies were not protective. As a consequence, virus-free animals subsequently infected with MnPV still accumulated high numbers of transcriptionally active viral genomes, ultimately leading to skin tumor formation. In contrast, vaccination with L1SHORT was completely protective. This shows that papillomavirus L1LONG expression is a unique strategy to escape from antiviral immune surveillance.